2016
DOI: 10.1016/j.accfor.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Conforming to accreditation in Iranian hospitals

Abstract: This paper examines the operation of an accreditation programme for hospitals in Iran. It explores the process of accreditation as a regulatory control system and analyses hospitals' responses to this type of control. We draw on the notion of steering and argue that the accreditation system is transactional in nature. Our findings show that hospitals conform to the scheme, although they also resist some of its requirements. On a wider policy level, we suggest that accreditations offer the accreditor the opport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 72 publications
0
19
0
2
Order By: Relevance
“…Most steering mechanisms combine diverse transactional and relational elements, existing somewhere along a continuum of possibilities, with the pure forms of transactional and relational steering at each extreme (Broadbent and Laughlin, ). Moreover, transactional steering does not always operate purely in a ‘command and control’ manner, because the means or processes in working towards the goals required by regulations may be underpinned by shared values (Agrizzi et al ., ).…”
Section: Theoretical Frameworkmentioning
confidence: 97%
See 2 more Smart Citations
“…Most steering mechanisms combine diverse transactional and relational elements, existing somewhere along a continuum of possibilities, with the pure forms of transactional and relational steering at each extreme (Broadbent and Laughlin, ). Moreover, transactional steering does not always operate purely in a ‘command and control’ manner, because the means or processes in working towards the goals required by regulations may be underpinned by shared values (Agrizzi et al ., ).…”
Section: Theoretical Frameworkmentioning
confidence: 97%
“…This is akin to the regulatory relationship inherent in a contract to undertake a particular project over a defined period. Previous literature has suggested that transactional steering may achieve its societal goals through the forces of law and funding (Agrizzi et al ., ; Fiondella et al ., ).…”
Section: Theoretical Frameworkmentioning
confidence: 98%
See 1 more Smart Citation
“…Such basic requirements could be related to space and building such as a separate entrance for emergency department (ED), minimum of 9 m 2 space per bed in any inpatient room, etc 12 or human resources that hospitals have no or less control over them. 13 Against this kind of standards, hospitals may resist or game because they could not make necessary changes easily. 13,14 Moreover, we know that the effectiveness of Iranian hospital accreditation comes from its pay for performance (P4P) policy, according to which the audit scores would define hospitals' level of charges.…”
mentioning
confidence: 99%
“…13 Against this kind of standards, hospitals may resist or game because they could not make necessary changes easily. 13,14 Moreover, we know that the effectiveness of Iranian hospital accreditation comes from its pay for performance (P4P) policy, according to which the audit scores would define hospitals' level of charges. 15 Such P4P policy conflicts with the MoHME's interests; MoHME I n a recent contribution to the ongoing debate about the role of power in global health, Gorik Ooms emphasizes the normative underpinnings of global health politics.…”
mentioning
confidence: 99%